Kesan Persekitaran Kerja Dan Tekanan Peranan Terhadap Prestasi Kerja Dalam Kalangan Jururawat : Kerohanian Sebagai Penyederhana - Mohd Isa, Nurul Hanun (2022)
The main purpose of this study is to determine whether the concepts found in the work condition that is opportunities, activities, information, supervision and support and role stress that is the inter-role distance, role overload and role of conflict affects the dimensions of job performance that is the provision of information, coordination care, social support and patient care and whether spirituality can affect the role stress on job performance.